Centre‐level variation in dental treatment and oral health and individual‐ and area‐level predictors of oral health in 5‐year‐old children with non‐syndromic unilateral cleft lip and palate: the Cleft Care UK study. Part 3. (June 2017) - Smallridge, J.; Wills, A. K.; Mahmoud, O.; Chong, A.; Clark, V.; Collard, M.; Sandy, J. R.; Ness, A. R.
Structured Abstract: Objectives: To explore centre‐level variation in fluoride treatment and oral health outcomes and to examine the association of individual‐ and area‐level risk factors with dental decay in Cleft Care UK (CCUK). Setting: Two hundred and sixty‐eight 5‐year‐old British children with non‐syndromic unilateral cleft lip and palate (UCLP). Materials and Methods: Data on caries and developmental defects of enamel (DDE) were collected. The child's history of fluoride ingestion and postcode was used to assess exposure to fluoridated water. Centre‐level variation in fluoride exposure and caries was examined using hierarchical regression. Poisson regression was used to estimate the association between individual‐ and area‐level fluoride exposures and outcome. Results: Children had high levels of caries, rampant caries and DDE. There was no evidence of variation between centres in the number of children with caries or rampant decay. There was evidence of variation in prescription of fluoride tablets and varnish and the type of toothpaste used. Area level of deprivation was associated with a higher risk of dental caries—risk ratio (RR) in the lowest quartile versus the rest was 1.43 (95% CI 1.13 to 1.81). Use of fluoride tablets and varnish was associated with higher risk of caries—RR 1.73 (95% CI 1.29 to 2.32) and RR 1.33 (95% CI 1.04 to 1.70), respectively, adjusted for age, sex and deprivation. Conclusion: The association with use of fluoride tablets and varnish probably reflects reverse causality but indicates the need for early preventative interventions in children with UCLP.